Estimated Glomerular Filtration Rate and Systolic Time Intervals in Risk Stratification for Increased Left Ventricular Mass Index and Left Ventricular Hypertrophy. Issue 10 (March 2016) - Lee, Wen-Hsien; Hsu, Po-Chao; Chu, Chun-Yuan; Chen, Szu-Chia; Lee, Hung-Hao; Lee, Meng-Kuang; Lee, Chee-Siong; Yen, Hsueh-Wei; Lin, Tsung-Hsien; Voon, Wen-Chol; Lai, Wen-Ter; Sheu, Sheng-Hsiung; et al.
Abstract : Abstract: Either decreased renal function or increased systolic time interval is associated with cardiac hypertrophy and poor cardiac outcome. The aim of this study was to evaluate combination of renal function and brachial systolic time intervals were associated with increased left ventricular mass index (LVMI) and left ventricular hypertrophy (LVH). In total of 990 patients were consecutively included in this study from January 2011 to December 2012. All study participants were further classified into 4 groups by the values of estimated glomerular filtration rate (eGFR) and ratio of brachial preejection period (bPEP) to brachial ejection time (bET). The classification of 4 groups were eGFR ≥ 45 mL/min/1.73 m 2 and bPEP/bET < 0.38 (group 1), eGFR ≥ 45 ml/min/1.73 m 2 and bPEP/bET ≥ 0.38 (group 2), eGFR < 45 mL/min/1.73 m 2 and bPEP/bET < 0.38 (group 3), and eGFR < 45 mL/min/1.73 m 2 and bPEP/bET ≥ 0.38 (group 4), respectively. Patients in groups 1 and 4 had the lowest and highest LVMI among 4 groups, respectively ( P < 0.001). In multivariable analyses, increased LVMI and LVH were significantly associated with patients in groups 2, 3 and 4 (vs group 1) ( P ⩽ 0.019). Our study demonstrated that joined parameter of renal function and systolic time intervals, in terms of eGFR and bPEP/bET, might be an alternative method in risk stratification for increased LVMI and LVH.